Emerged Pleistocene marine deposits of Peary Land (North Greenland) - Laursen, Dan (Meddelelser om Grønland, 2026)
Based on investigations already published and recent field work on Peary Land, North Greenland, the writer gives an account of the emerged marine deposits and the shells found in them. Measurements showing the emergence and in this connection some reflections concerning the upper marine limit are given. The fauna is typical of the Arctic but the presence of Lima subauriculata (MONT.) on the north coast of Peary Land makes an earlier milder climate possible; most likely the upper marine limit is to be found at a higher level than previously supposed.